Paul Tillich and pentecostal theology : spiritual presence and spiritual power - Wariboko, Nimi, 1962-; Yong, Amos (Indiana University Press, 2015)
Paul Tillich (1886-1965) is widely regarded as one of the most influential theologians of the 20th century. By bringing his thought together with the theology and practices of an important contemporary Christian movement, Pentecostalism, this volume provokes active, productive, critical, and creative dialogue with a broad range of theological topics. These essays stimulate robust conversation, engage on common ground regarding the work of the Holy Spirit, and offer significant insights into the universal concerns of Christian theology and Paul Tillich and his legacy.